Central station for small country village telephone exchange - Wood, Thomas M. (My University, 1906)
Introduction: Visitors at the Centennial Exhibition in 1876 were astonished on hearing the voices of friends brought to them over a wire that extended the length of Machinery Hall - a distance of but a few hundred feet. Today, it is possible to talk between Omaha and New York , a distance of fifteen hundred miles. Scarcely more than a decade ago, the telephone was regarded as a luxury. Today it has become a business and, almost a household necessity. Millions of capital are invested in the telephone industry and employment is furnished to thousands. Nearly every country village and hamlet has its telephone exchange. Farm lines extend every where. The country is being bound into one great community. Man's horizon is broadening. The telephone is bringing man into closer touch with his fellows, is fostering feelings of interdependence, and helping to unite him into one common brotherhood. For each subscriber to have facility to call up directly any other subscriber, would require so many lines as to make the scheme impracticable, if not impossible. To obviate this, some central point to which all lines converge and where connections may be made between any two of them, must be chosen. Such a point is called a Central Station or Central. The location of central is an important factor in the building and maintenance of a telephone exchange. It should be located at what is called the telephonic center. This is such a point at which all subscribers can be reached by the use of the least possible amount of wire. In the location of this point, not only present conditions but also future developments must be considered. It is evident, that the proper location of central will minimize the cost of installation, the loss in depreciation, and the expense of maintenance.
Citation: Wood, Thomas M. Central station for small country village telephone exchange. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Telephone Exchange; Telephone; Specificatfions; Blueprints; Equipment; Theses